The role of loose parts play in logical thinking skill in KB Lab school - Shabrina, Ega; Lestariningrum, Anik (JECCE (Journal of Early Childhood Care and Education), 2020)
Logical thinking is a pivotal skill for children that must be developed as early as possible in order to prepare an ability to think realistic and systematic. Think logically somehow is difficult for age 3-4 years old shown by facts that some children only do activities based on teacher’s example. Loose part play was selected because it facilitates creative, logical, and systematic thinking in problem solving. Loose part play is one activity that uses concrete and real object to explore. Using qualitative approach, this study involves ten students from KB Lab school. The result was analyzed using qualitative descriptive method. The data were collected using observation, interview, and documentation. The result of the study showed that the 3-4 years old children showed an improvement after playing loose part because the activities suits their developmental stage and utilized objects in their surroundings.